Preparation and characterisation of Nanolignin-Gelatine-Glycerol Composite (NLGGCs) thin film for food coating application - Rafiae, Nur Najmina; Hafi Othman, Muhammad Bisyrul; Abdullah Sani, Muhamad Shirwan; Mohamad Ibrahim, Mohamad Nasir; Mohamad Daud, Najwa Najihah (IIUM Press, 2024)
Recognising the importance of preventing rapid food deterioration and prolonging the shelf life of fruits and vegetables from oxidation, we successfully created thin films composed of Nanolignin-Gelatine-Glycerol Composites (NLGGCs) through a traditional blending technique. Fourier Transform Infrared Spectroscopy (FTIR) confirmed the successful preparation of nanolignin structures, with characteristic peaks observed at 513 cm-1 (C-C stretching in aromatic), 1222 cm-1 (phenolic OH), and 1107 cm-1 (Ar-H and syringyl group). Ultraviolet-visible spectroscopy (UV-Vis) revealed an absorption capacity within the 280 to 300 nm range. Film opacity increased with a greater nanolignin composition in the thin film, attributed to the presence of chromophore structures. Thermogravimetric Analysis (TGA) demonstrated a thermal degradation temperature exceeding 300°C. Differential Scanning Calorimetry (DSC) analysis unveiled two distinct glass transition temperatures (Tg) at approximately 60°C and 80°C, indicating microphase separation and immiscibility between gelatine and nanolignin particles. The nanolignin content significantly influenced solubility and water uptake, with higher nanolignin content leading to reduced solubility and water absorption. The application of NLGGCs film coatings on banana surfaces extended their shelf life compared to control samples after 10 days. Furthermore, NLGGCs underscore the pivotal role in enhancing the performance as a promising bio-based food coating alternative for future applications.